Turning hills into mountains? Current commitments under the GATS and prospects for change - Rudolf Adlung; Martin Roy (World Trade Organization (WTO), 2005)
Over the past months, it has become increasingly clear that the services negotiations under the Doha Development Agenda will not produce significant improvements on current commitments unless major new impetus is provided. In an introductory section, this paper discusses various impediments, from the perspective of participating governments, that may explain the lack of negotiating momentum to date. It then provides an overview of existing commitments under the GATS (by sector, mode of supply, and level of development) and of the initial offers that had been tabled by early 2005. Despite the substantial benefits that may be associated with the liberalization of services trade, the GATS has obviously not yet lived up to ambitious expectations. For example, on average across all WTO Members, only one-third of all services sectors have been included in current schedules of commitments; and many entries have been combined with significant limitations on market access and national treatment or with the complete exclusion of particular types of transactions (modes of supply) from coverage. While the ongoing services negotiations provide an opportunity to complement the rule-making efforts of the Uruguay Round with genuine market opening, many governments apparently have found it difficult, despite generally more restrictive access regimes and, thus, potentially higher gains from liberalization than in merchandise trade, to undertake or envisage economically significant bindings across a broad range of services. Five years after the inception of the services round, current negotiating arrangements, based mainly on (bilateral) exchanges of requests and offers, may need to be complemented by common points of reference to provide greater focus and guidance.
Keywords: D78; F10; F13; F2; 330; WTO; trade in services; trade negotiations; liberalization; GATS; Welt